Genetic variation and population structure of brachiopods, Lingula anatina Lamarck, 1801 in the Northern Aceh shore, Indonesia - CHITRA OCTAVINA; MUTIA RAMADHANIATY; RAHMA EFFENDIE DAULAY; IRMA DEWIYANTI; MARIA ULFAH (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Octavina C, Ramadhaniaty M, Daulay RE, Dewiyanti I, Ulfah M. 2023. Genetic variation and population structure of brachiopods, Lingula anatina Lamarck, 1801 in the Northern Aceh shore. Biodiversitas 24: 3951-3959. Lingula anatina is one of the brachiopods recognized as one of the most primitive groups with a fossil record from the early Cambrian period. Although L. anatina has been targeted as an object of biological studies, the information about the genetic variation within species is still limited. The purpose of this research is to identify the genetic variation and population structure of the species L. anatina found in the Aceh northern shore based on the mtDNA Cytochrome Oxidase I (COI) gene sequence. In this study, L. anatina specimens collected from five populations on Aceh's northern shore, namely Krueng Raya, Syiah Kuala, Ulee Lheue, and Ujong Pancu, with complete mitochondrial genome sequences were analyzed and compared with genebank sequences. The total nucleotide base of L. anatina is 657 bp, with 18 haplotypes. Based on the results of a comparison of the distribution of L. anatina in Asia shows that the Japanese population has the highest population structure value compared to the other five populations. The Fst value obtained from this study is 0.7, so it is classified as high and structured. Phylogenetic analysis showed that the correlation between geographic location and geographic distance affects the genetic distance between populations.